Characteristics of COVID-19 infection in Primary Healthcare in Belgrade, Serbia and influence of socio-demographic features of the participants on vaccination status: (General Practice, 2023)
Introduction. The coronavirus pandemic began in 2019and since then a huge number of people have been infectedworldwide. The infection symptoms are widely defined andyet the panel of laboratory abnormalities found in infectedpatients is missing.Objective. We aimed to describe the clinical and laboratoryfeatures of the COVID-19 patients in Belgrade (Serbia)and the influence of socio-demographic features of theparticipants on vaccination status.Method. The research was performed as a cross-sectionalstudy from October to November 2021. The includedpatients were the ones who visited the COVID outpatientclinic of the Primary Healthcare Center (PHC) and testedpositive for Sars-CoV-2 virus infection. The data were gatheredby reviewing retrospectively the patients` health charts.The data were analyzed by descriptive statistics, Pearson`s χ2test, and we used the SPSS 20.Results. The research included 207 Sars-CoV-2 positivepatients, of whom 56% were of the female sex and themajority of the participants were in the 51–60 age group(22.7%). There were 42% of the vaccinated participants.The most common symptoms the participants complainedof were: fever (82.1%), cough (49.8%), malaise (32.9%),stuffed nose (29.5%), throat pain (17.9%), headache (12.1%),body pains (11.1%), loss of smell and taste (8.2%), diarrhea(2.4%). Pneumonia was found in 17.4% of the participantsand high CRP values in 29%.Conclusion. The most common clinical features of theCOVID-19 patients in Belgrade (Serbia) were fever, cough,and malaise. Pneumonia was found in 17.4% of the patients.The majority of the patients had normal lab work but 29%had elevated CRP. There were 42% of vaccinated patientswith either of the four available vaccines and 52.9% werewithout comorbidities.
Keywords: COVID-19; clinical features; CRP; vaccination